HUBUNGAN STATUS SOSIAL EKONOMI ORANG TUA DENGAN PERILAKU PROSOSIAL ANAK USIA 5-6 TAHUN DI TK TAMAN RAUDAH PEKANBARU - Asril, Suci Pratiwi; Chairilsyah, Daviq; Hukmi, Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : The background of the problem of this study aims to determine the relationship of socio-economic status with prosocial behavior of children aged 5-6 years in Pekanbaru Taman Raudah Kindergarten. This study is a correlation study using the chi square technique through the observation sheet of children's prosocial behavior. The sample used in this study were 30 children with a population of children aged 5-6 years with 30 children. The data collection techniques used are observation. The data analysis technique uses the chi square test using the SPSS Statistic Ver program. 22 which is done through the results of the analysis of the description of each variable and the results of correlation analysis between variables. The results of the analysis and processing of data obtained by the average score, standard deviation, mode value and median value. Based on the results of data analysis obtained Next to find out how much the relationship of socio-economic status of parents with prosocial behavior of children, researchers conducted a test of correlation analysis with Chi Square test. On the results of the correlation test obtained a probability number of 0,065, where 0,065 is smaller than 0,05 (0,065 <0,05), then Ho is rejected, meaning there is a significant relationship between socio-economic status and prosocial behavior. The correlation coefficient produced is equal to 0,435. Then it can be concluded that there is a relationship between the socio-economic status of parents with prosocial behavior of children aged 5-6 years in Taman Raudah Kindergarten in Pekanbaru. This can be seen from the magnitude of the relationship between socio-economic status and the prosocial behavior of children using the chi square formula that is equal to 59,17% in the fairly good category.Keywords: Prosocial Behavior, Parents' Socio-Economic Status